INTEGRATED COMMUNITY EMPOWERMENT: LEARNING FROM THE COMPANY'S EXPERIENCE IN EMPOWERING COMMUNITIES IN COASTAL AREAS - Ratri Utami, Annisa; Adhi Kelana, Dimas; Larasati, Zita Wahyu (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The vulnerability experienced by the community around the company's offshore operations has prompted PT Pertamina Hulu Energi Offshore North West Java (PHE ONWJ) to develop an empowerment program that focuses on improving community welfare and environmental sustainability. One of them is by tackling the problem of abrasion by developing an integrated community empowerment program or commonly known as the Environmentally Based and Creative Economy-Based Coastal Area Management Program (PASIR BERBISIK) in Pasir Putih Hamlet. Through the BERBISIK PASIR Program, the community is invited, involved, and trained to be able to solve and handle all existing socio-economic and environmental problems by utilizing all the potential and opportunities around them independently. Through the BERBISIK PASIR program, PHE ONWJ integrates coastal area management through various sub-programs, such as Mangrove Ecotourism Area Management, Empowerment of Fishermen's Wives SMEs, Coastal Waste Management, and Environmentally Friendly Crab Catching Education. This journal looks at the impact of an integrated community empowerment program that can be felt both by the community and the environment.